Employee Recruitment Process Based On Dessler's Theory (2013) At Uddan Store: A Grounded Theory Study - Prastiono, Suryo; Sudarmiatin; Puji Handayati; Naswan Harsono (International Journal of Business and Quality Research, 2025)
This study aims to gain an in-depth understanding of the recruitment process at Toko Uddan, a small business in the goods distribution sector, using a qualitative approach and grounded theory analysis. Data was collected through in-depth interviews with the owner, administrator, field coordinator, and employees. The results of the study show that recruitment at Toko Uddan is simple, flexible, and greatly influenced by social proximity. Candidates are obtained almost entirely through family and relative recommendations, while selection is conducted informally by considering personality, work ethic, and readiness to start working immediately. Orientation is provided through a one-week field trial period without formal training. Through open coding, axial coding, and selective coding, this study produced a Relational-Operational Recruitment model consisting of three core categories: trust-based recruitment, personality- and work readiness-based selection, and rapid placement through hands-on practice. When compared to Dessler's (2013) recruitment theory, Toko Uddan's recruitment practices show significant differences in terms of formality, diversity of applicant sources, and objectivity of selection, but remain effective in the context of SMEs. The validity of the findings is maintained through the application of Lincoln and Guba's (1985) criteria, including credibility, transferability, dependability, and confirmability. These findings make an important contribution to understanding relationship-based recruitment patterns in small businesses in Indonesia and their implications for more adaptive and contextual human resource management